Topotecan plus cyclophosphamide in adults with relapsed or refractory pediatric-type sarcoma: a retrospective analysis from the German Sarcoma Medical Oncology Group (AIO) - Hartmann, Joerg Thomas; Issels, R. D.; Nicolo, K. San; Gruenwald, V.; Hertenstein, B.; Papesch, E.; Krause, Stefan; Sturm, I. (Investigational New Drugs, 2015)
To assess the efficacy and safety of topotecan and cyclophosphamide (TC) in adult patients with pediatric-type sarcoma subtypes who failed induction chemotherapy.Patients with pediatric sarcoma subtypes, refractory to or relapsed after at least one prior induction chemotherapy, inoperable, ECOG PS 0-2, with measurable, progressive disease (PD), adequate organ functions, who have been treated with TC combination were retrospectively analysed within the AIO and SAREZ/BMBF network.Thirty-nine patients, median age 28 years (18-58), 14 females, 25 males, have been identified. All patients had received induction treatment according to (inter)national study protocols. Second-line TC was applied in 33 patients (>=3rd-line in 6 patients). Twenty-three patients had refractory disease (evidence of PD during induction chemotherapy); 8 patients experienced an early relapse within 6 months as well as 8 patients after more than 24 months (late relapse). A median of 3 cycles (range, 1-6) had been applied and antitumor activity was: CR 2.6 %, PR 7.9 %, and disease stabilisation (SD) 26.3 %. PR lasted 32.8 months and median duration in patients with SD was 5 months (range, 2.0-14.7). The 3/6-months progression-free rates were 43.2 and 18.9 %.Limited activity was seen in adult pts with refractory or relapsed pediatric-type sarcomas with the regimen which has proven activity in pediatric patients. Adults with refractory small cell sarcoma appear to have a similar dismal outcome as seen in pts with common adult-type histologies; however, a subset of patients has achieved long-lasting remissions on TC resulting in long-term survival.
EVALuna2:25725